Pemenuhan Kebutuhan Dasar Lanjut Usia Terlantar di Lembaga Kesejahteraan Sosial Pondok Berdikari Tangerang - Ero Ayu Ajeng Bahrudin; Almisar Hamid (Sosial Simbiosis : Jurnal Integrasi Ilmu Sosial dan Politik, 2025)
Fulfillment of basic needs of the elderly consists of physical and psychological needs. However, currently, neglect of the elderly in society is rampant so that their physical, mental, and emotional needs are not met which results in the quality of life of the elderly being disturbed. This study aims to analyze the fulfillment of basic needs of neglected elderly in the Elderly Social Welfare Institution, with a case study at Pondok Lansia Berdikari. This study uses a qualitative research approach and Purposive Sampling sampling technique involving 3 respondents. Data were collected using in-depth interviews, observations, and documentaries. Data were analyzed using the Interactive, Miles and Huberman analysis models. The results of the study indicate that the fulfillment of physical and psychological needs of neglected elderly in Pondok Lansia Berdikari is fulfilled with a comfortable environment, controlled temperature, adequate lighting, minimal noise, and attention to nutritional intake and hydration. On the psychological side, recreational activities and opportunities for social interaction are provided that support the emotional well-being of the elderly. However, the fulfillment of psychological needs in terms of religion has not been fully met due to limited facilities for places of worship, although religious programs have been available. Thus, the needs of the elderly are physically met but in terms of religious psychology they have not been met. Therefore, it is necessary to provide worship facilities for the elderly.